Autocontrole e escolhas intertertemporais: uma análise dos efeitos da alegria e diversão nas representações mentais - Henz, Miriam Mariani (Universidade do Vale do Rio dos Sinos, 2020)
This thesis aimed to analyze the effect of joy and amusement on mental representations of distances originated by situations of consumption self-control. The present work extends the previous researches and unites the theoretical currents of self-control, Construal Level Theory (CLT) and positive emotions. In four studies (one pilot and three experimental) carried out in person, it was demonstrated that the incidental emotions of joy (studies 1 and 2) and amusement (studies 1 and 3) moderate the mental representations of intertemporal choices. The results showed that the moderation of joy occurs under low emotional intensity and the moderation of amusement occurs both in low and high intensity. These two emotions share a positive assessment of the dimension of certainty regarding understanding and clarity of what is happening in the present and what can be predicted for the future. Specifically, joy, it also has positive associations with dimensions of agency and personal control that promote the ability and ease to resolve conflicts, trust and perseverance in the pursuit of goals. Amusement does not share these dimensions with joy and is positively related to attentional activity, which captures new and unexpected environmental clues. It is also linked to the ability to cope and the cognitive management of events with the potential to threaten well-being. The set of these characteristics must have favored the moderating effect of joy and amusement in the relationship of self-control and intertemporal choices, with the preservation of long-term interests. In addition, this research investigated five other positive emotions, namely, contentment, pride, love, compassion and admiration (study1), with the adoption of the Dispositional Positive Emotion Scale (DPES), which did not have a moderating effect on the investigated relationship. This study brings contributions to the literature that investigates consumer self-control behavior and positive emotions, proving that specific positive emotions can have different influences. When applying the CLT lens for the self-control exam, the results show that the moderating effect of joy and amusement depends on the level of construction and interpretation attributed to the choices in question. Taken together, these findings contribute to marketing professionals (i) in the definition of strategies for future consumption offers (ii) with support actions that include joyful and amusement experiences to facilitate the exercise of self-control and (iii) actions of relationship to strengthen the bonds between the company and the consumer. Likewise, the findings can be used by public policy makers to suggest proposals that consider individual differences and include emotional experiences of joy and amusement in behavioral changes that require self-control.
Keywords: Autocontrole; Representações mentais; Distância temporal; Alegria; Diversão; Self-control; Mental representations; Temporal distance; Joy; ACCNPQ::Ciências Sociais Aplicadas::Administração